2022
DOI: 10.3389/fmicb.2022.799819
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of the miRNAome and Transcriptome Reveals miRNA–mRNA Regulatory Networks in Catharanthus roseus Through Cuscuta campestris-Mediated Infection With “Candidatus Liberibacter asiaticus”

Abstract: Citrus Huanglongbing (HLB) is the most devastating disease of citrus caused by the Gram-negative phloem-limited bacterium “Candidatus Liberibacter asiaticus” (CLas). It can be transmitted by the Asian citrus psyllid “Diaphorina citri,” by grafting, and by the holoparasitic dodder. In this study, the non-natural host periwinkle (Catharanthus roseus) was infected via dodder (Cuscuta campestris) from CLas-infected citrus plants, and the asymptomatic leaves (AS) were subjected to transcriptomic and small-RNA profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
(66 reference statements)
0
2
0
1
Order By: Relevance
“…Liberibacter asiaticus” pathogenic effectors ( 14 ), and analyses of “ Ca . Liberibacter asiaticus”-host interaction ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Liberibacter asiaticus” pathogenic effectors ( 14 ), and analyses of “ Ca . Liberibacter asiaticus”-host interaction ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the rapid establishment and multiplication of CLas, and shortening latency for symptoms development induced by CLas, periwinkle is commonly used for studies of CLas ( Zheng et al, 2014 ; Li et al, 2021 ; Killiny, 2022 ). A recent study found that the miRNA–mRNA regulatory mechanism involved in plant defense responses, regulation of secondary metabolism, and nutrient homeostasis plays an important role in periwinkle–CLas interaction ( Zeng et al, 2022 ). In addition to acting as a transmission tool for CLas, dodder can be also used as an appropriate plant host for CLas multiplication ( Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de los esfuerzos por mitigar la enfermedad, hasta la fecha no hay variedades con resistencia real, ni tratamientos efectivos para eliminar el HLB en ninguna especie de cítricos (Gao et al, 2018). Por ello, se han buscado estrategias para elucidar el mecanismo regulatorio de la enfermedad, siendo las aproximaciones "ómicas" (genómica, transcriptómica, metabolómica) las más utilizadas en los últimos años (Ventura-Medina et al, 2019;Zeng et al, 2022). Con la ayuda de tecnologías como RNA-Seq, actualmente es posible caracterizar el transcriptoma de plantas de manera rápida y con una mayor sensibilidad, lo que ha supuesto un cambio relevante en el estudio de plantas no modelo ante el estrés biótico y abiótico.…”
unclassified